2014
DOI: 10.1016/j.ffa.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic functions and maximal Artin–Schreier curves

Abstract: For an odd prime p and an even integer n with gcd(n, p) = 1, we consider quadratic functions from F p n to F p of codimension k. For various values of k, we obtain classes of quadratic functions giving rise to maximal and minimal Artin-Schreier curves over F p n . We completely classify all maximal and minimal curves obtained from quadratic functions of codimension 2 and coefficients in the prime field F p .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…If we take all the coefficients s i of S(x) in F q m we obtain the following explicit classifications in Corollaries 1, 2 and 3. These results include the maximal curves obtained in [2] as a very special subcase. Also note that in [2] only the case q = p (prime case) is considered under the condition that gcd(p, n) = gcd(p, 2m) = 1.…”
Section: Preliminariesmentioning
confidence: 79%
See 3 more Smart Citations
“…If we take all the coefficients s i of S(x) in F q m we obtain the following explicit classifications in Corollaries 1, 2 and 3. These results include the maximal curves obtained in [2] as a very special subcase. Also note that in [2] only the case q = p (prime case) is considered under the condition that gcd(p, n) = gcd(p, 2m) = 1.…”
Section: Preliminariesmentioning
confidence: 79%
“…These results include the maximal curves obtained in [2] as a very special subcase. Also note that in [2] only the case q = p (prime case) is considered under the condition that gcd(p, n) = gcd(p, 2m) = 1. Here we have no such condition.…”
Section: Preliminariesmentioning
confidence: 79%
See 2 more Smart Citations
“…We start with a discussion of the case h = 0, and then turn our attention to R(X) = X p h . For more results along the same lines we refer to [3] and [1]. In [4] it is shown that all curves C R that are maximal over the field F p 2n are quotients of the Hermite curve H p n with affine equation y p n − y = x p n +1 .…”
Section: Examplesmentioning
confidence: 99%